Efektivitas Penyaluran Dana STF Presfektif Maqashid Syariah Terhadap Pengembangan Kinerja Usaha Ultra Mikro - Faizin, Muhammad Agus Izzi (ITB AAS INDONESIA Surakarta, 2024)
The Social Trust Fund is a Dompet Dhuafa financing program using the Qardhul Hasan contract that aims to develop the community to carry out ultra-micro activities. The purpose of this study is to analyze the effectiveness of the STF program on the development of ultra-micro activities before and after getting STF funds from the maqashid sharia review. The methodology used is a qualitative approach by analyzing instrument data in the form of interviews with Qardhul Hasan fund managers, Ultramikro actors, and documentation owned by Dhuafa wallets. The results of the study found that the effectiveness of the program has almost achieved the overall goal; this is indicated by Iqamah al Adl and Jalb al Maslahah's feelings for Ultramikro actors, while for Tahdib al Fard, Ultramikro actors have not felt the benefits of this program. This research can be used as an evaluation for Dhuafa wallet managers to improve the fund management system so that the objectives of this program are achieved as a whole